Evaluation of the ability of bone marrow derived cells to engraft the kidney and promote renal tubular regeneration in mice following exposure to cisplatin. (20th April 2016) - Bataille, Aurélien; Galichon, Pierre; Wetzstein, Morgane; Legouis, David; Vandermeersch, Sophie; Rondeau, Eric; Hertig, Alexandre
Abstract: It has been suggested that bone marrow derived stem cells have the ability to engraft the kidney and improve the outcome of severe acute kidney injury (AKI) in mice exposed to high doses of cisplatin, providing hope for cancer patients in whom irreversible renal damage occasionally occurs following the use of this highly effective anti-tumor drug. We tested the therapeutic potential of bone marrow derived cells injected during the acute phase (day 3 after cisplatin administration) of experimentally-induced AKI in C57Bl6/J mice, characterized by massive tubular necrosis, apoptosis, and a low proliferation capacity. We failed to show any benefit of bone marrow derived cells versus a regular homogenate of intact renal cells, or normal saline. Using cell tracers and flow cytometry, we demonstrated that bone marrow derived cells did indeed home to the bone marrow of the recipients but failed to settle in the kidney. Conversely, renal cells homed to injured kidneys. However, neither cell therapy protected the animals against cisplatin-induced death. We therefore question the short-term efficacy of bone marrow derived cells used to repair established injuries of the tubular epithelium.